A critical analysis of the models connecting molecular mass distribution and shear viscosity functions (eXPRESS Polymer Letters)
Thermoplastics having various short and long-chain branches, characterized by the melt index measured at the processing temperature – according to their average molecular mass – can be processed using universal principles, independently of their chemical composition. The average molecular mass is the result of a molecular mass distribution, being the fingerprint of the chemical synthetic technology. The actual shape of the shear viscosity function aiming at the quantitative characterization of viscous flow, containing material-dependent parameters, depends on the ratio of high and low molecular mass fractions, the width of the molecular mass distribution function and on the number of short and long chain branches. This publication deals with the critical analysis of the mathematical methods of transforming these two curves of basic importance into each other.